Effect of Educational Training on Nutrition and Weight Management in Elite Spanish Gymnasts - Visiedo, A.; Frideres, J. E.; Palao, J. M. (Central European Journal of Sport Sciences and Medicine, 2021)
The aim was to study the effect of a formative program about nutrition as well as weight management and its risks in elite gymnasts. The sample was 37 under-18 Spanish athletes from rhythmic and aesthetic gymnastics (national level). The sample was divided into a control group (n=21) and an intervention group (n=16). A quasi-experimental design with a pre-test and post-test was used. The dependent variable was the knowledge of nutrition, weight management, and its risks. The independent variable was the educational program. The program had three 30-minute sessions which combined talks, videos, and tasks to complete. Descriptive and inferential analyses were done. The educational program was ineffective with regard to increasing the gymnasts` knowledge about nutrition, weight management, and its risks. The gymnasts` knowledge of nutrition and weight management was high before beginning the intervention. Gymnasts and the coach expressed the need for individualized training adapted to each gymnast`s needs and for incorporating a follow-up that provides feedback that is applicable in the gymnast`s daily life